On the dynamics of interstate migration: migration costs and self-selection - Christian Bayer; Falko Juessen (Institute for the Study of Labor (IZA), 2008)
This paper develops a tractable dynamic microeconomic model of migration decisions that is aggregated to describe the behavior of interregional migration. Our structural approach allows us to deal with dynamic self-selection problems that arise from the endogeneity of location choice and the persistency of migration incentives. Keeping track of the distribution of migration incentives over time has important consequences for the econometrical treatment, because the dynamics of this distribution influences the estimation of structural parameters, such as migration costs. For US interstate migration, we obtain a cost estimate of less than one-half of an average annual household income. This is substantially smaller than the migration costs estimated by previous studies. We attribute this difference to the treatment of the dynamic self-selection problem.
Keywords: C61; 330; Dynamic self-selection; migration; indirect inference; Binnenwanderung; Kosten; Wohnstandort; Dynamisches Modell; Theorie; USA